2021
DOI: 10.1021/acsabm.1c00307
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans Can Survive Antifungal Surface Coatings on Surfaces with Microcone Topography

Abstract: This study demonstrates the ability of Candida albicans, a medically significant human fungal pathogen, to minimize contact with an antifungal surface coating that on a flat surface is lethal on contact by growing on and between micron-sized surface topographical features, thus minimizing the contact area. Scanning electron microscopy showed that cells contacting the “floor” between microcones were killed, whereas cells attached to microcones survived and formed hyphal filaments. These spanned space between co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Plasma polymer surfaces grafted with caspofungin were tested for antifungal surface activity using a modified static biofilm assay (SBA) on Thermanox substrates. [ 65 ] To elucidate anti‐fungal surface efficacy of caspofungin grafted gly pp coatings, Candida albicans SC5314 biofilms were adhered on cw + caspo and cw + pw + caspo coatings and on control samples that included Thermanox substrates (Thermo Fischer Scientific, Australia), cw and cw + pw gly pp surface coatings. The growth of C. albicans was carried out thrice on Spider media following culture revival from −80°C to ensure full fungal activity.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma polymer surfaces grafted with caspofungin were tested for antifungal surface activity using a modified static biofilm assay (SBA) on Thermanox substrates. [ 65 ] To elucidate anti‐fungal surface efficacy of caspofungin grafted gly pp coatings, Candida albicans SC5314 biofilms were adhered on cw + caspo and cw + pw + caspo coatings and on control samples that included Thermanox substrates (Thermo Fischer Scientific, Australia), cw and cw + pw gly pp surface coatings. The growth of C. albicans was carried out thrice on Spider media following culture revival from −80°C to ensure full fungal activity.…”
Section: Methodsmentioning
confidence: 99%
“…Besides aldehyde plasma polymer coatings, covalent attachment could be facilitated by linking caspofungin's amine groups to epoxide groups present on plasma polymers from continuous and pulsed deposition of allyl glycidyl ether [ 100 ] or glycidol. [ 101 ] The latent reactivity of intact epoxide groups on these plasma polymers allowed for strong covalent bonds to be formed without the need for a second chemical step.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…In addition, C. albicans cell wall may be too thick for the tip of the microcone silicon surfaces (tip width: 1-10 nm) to penetrate. [37] Valdez-Salas et al demonstrated that Ti nanotubes may disrupt C. albicans nanoadhesion bonds at the biointerface and hypothesized that the surface topography and structural orientation play a crucial role in reducing C. albicans attachment. [38] Herein, in light of the mechano-bactericidal action of nanostructured surfaces, we hypothesize that surface features in the order of microns could apply sufficient me-chanical force to the cell wall of Candida cells to promote cell lysis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, C. albicans cell wall may be too thick for the tip of the microcone silicon surfaces (tip width: 1–10 nm) to penetrate. [ 37 ] Valdez‐Salas et al. demonstrated that Ti nanotubes may disrupt C. albicans nanoadhesion bonds at the biointerface and hypothesized that the surface topography and structural orientation play a crucial role in reducing C. albicans attachment.…”
Section: Introductionmentioning
confidence: 99%